A RANGE OF NEW FUNCTIONAL APPLICATIONS TO THE BUILDING OF HERITAGE BANK INDONESIA - Devina Veronika, Yenny Gunawan (Riset Arsitektur (RISA), 2017)
Abstract - The city district known as Senen forms one of the historical parts of Jakarta where there are many buildings to be found in the Dutch East Indies Empire style as architectural relics of the Dutch Colonial Era, and the majority of these buildings are still there, up to the present. Many of these relics of the past have not been properly maintained and have suffered damage. One of these happens to be the Heritage Bank Indonesia building situated at Jalan Prapatan No.42 in Jakarta. After its conservation and re-use, a functional change has taken place that is quite drastic when considered from its establishment until the present. This research study can be categorized as qualitative. The research method consists of the descriptive method along with the analytical and interpretative methods. The data have been analyzed by drawing a comparison between the building in its initial state and its current condition, which was subsequently processed based on the conservation principles issued by the regional authorities called Perda. The data collection technique was employed with the observational method, interviews, taking measurements, and by way of studying the relevant background literature. The conclusion of this research study is that the building of the Heritage Bank Indonesia is nothing but a piece of sculpture after its conservation because it has become isolated or alienated from its surroundings, and as such it is no longer in keeping with its environmental context, which is situated in the Learning center complex of Bank Indonesia. Keywords: variety of new functional applications, Dutch East Indies Empire style of architecture, Heritage Bank Indonesia building